Photodynamic therapy based on organic small molecular fluorescent dyes - Li, Li; Chen, Yisha; Chen, Weijie; Tan, Ying; Chen, Haiyan; Yin, Jun (Chinese chemical letters, 2019)
This review aims to provide a summary of the progress in organic small molecular fluorescent dyes for photodynamic therapy in recent years and it is classified according to the structures of dyes including cyanines, phthalocyanine, BODIPYs and other agents. [Display omitted] Photodynamic therapy (PDT) has shown promise as an effective treatment modality for cancer and other localized diseases due to its noninvasive properties and spatiotemporal selectivity. Near-infrared (NIR) fluorescent dyes based on organic small molecules are characterized with low cytotoxicity, good biocompatibility and excellent phototoxicity, which are widely used in PDT. In this review, we attempt to summarize the development of imaging-induced PDT based on organic small molecules and classify it according to the structures of dyes including cyanines, 4,4-difluoro-4-bora-3a,4a-diaza-s-indacene (BODIPY) analogues, phthalocyanine and other agents such as rhodamine analogues.